Efforts in Reducing the Urge of Using Gadgets among Vocational High School Students - Jap Tji Beng; Sri Tiatri (Institute for Research and Community Services, 2020)
The role of vocational high schools in producing reliable workforce is highly expected. Gadgets are one of the tools used by vocational high school students in their daily lives. Gadgets can help in the learning process. However, there are indications that students tend to overuse gadgets. This overuse has caused problems, for example, in their social relationship. Efforts to reduce the use of gadgets are therefore needed so that the students are able to improve their skills in building a social relationship. This community service activity was intended to reduce the urge to use gadgets by students in their daily lives. The activity was divided into two parts. The first part included discussion with the principal and a teacher and the second part discussion with students. The participants of the activity were the school principal, a teacher, and 36 students of the vocational high school in Belitung. Interactive group discussions were used as the method in this program. In addition, a questionnaire was used to obtain a description of students’ experiences and their opinions about the time of using gadgets. The activity resulted in the decision made by the principal and the teacher to implement a plan to reduce the urge of using gadgets by students while at school. Students also tended to agree on reducing the urge to use gadgets. However, the maximum duration of time per day for students to be able to use gadgets still needed further discussion, because students inclined to disagree with the limit of three hours per day. From this activity it was concluded that the interactive discussions among researcher, principal, teacher, and students could reduce the urge to use gadgets by students while at school.